KEANEKARAGAMAN JENIS POHON PADA HUTAN TERGANGGU DI DAERAH KORIDOR TAMAN NASIONAL GUNUNG HALIMUN - Razali Yusuf (BERITA BIOLOGI, 2004)
A study on the disturbed forest in the corridor of Gunung Halimun National Park has been carried out in order to know the tree species diversity and species composition.The research located at the corridor area of Gn Halimun National Park around Purwabakti and Pulasari villages.The corridor area are roles as the bridge of flora between Salak mountain and Halimun mountain.The recorded tree species at 1 ha plot shows that from 441 individu was 69 species belong to 47 genera and 33 families.From 815 individu the recorded sapling 87 species belong to 68 genera in 40 families. Maesopsis eminii, is an introduced tree but in this study it was recorded as a very dominant species. Futhermore Lauraceae was reported as the biggest family with 9 species.Two species of Cyatheaceae, were encountered during the research, and this family namely Cyathea sp.and Cyathea contaminans has the biggest number of individu by having Family Importance Value (FIV) = 34.21 for tree and FIV = 42.11 for sapling. Fagaceae family was represented by the presence of Lithocarpus spicatus & Castanopsis gemelliflora, and it is as the next biggest number of individu 2 (FIV =31.66) and basal area is 2.7 m .